Study on the Physical Properties and Joint Evolution Characteristics of Three-Dimensional Reconstructed Coal - Yongning Wu; Zhe Zhang; Xinzhe Wang; Peiyang Zhu; Xin Yang; Lishuai Jiang (Advances in Materials Science and Engineering, 2021)
There are various complex joints (fissures), laminae, and other soft structural surfaces in the roadway enclosure, and the existence of these soft structural surfaces seriously affects the stability of the roadway enclosure. In order to study the mechanical properties of the coal body and the development of joints during coal fracture, this paper establishes a three-dimensional model of the fracture structure of the coal body based on CT scanning and three-dimensional reconstruction technology. On this basis, a 3D numerical model of the equivalent nodal coal body is constructed, uniaxial compression simulation analysis is performed, and the joint evolution development law of the coal sample is studied by the built-in joint monitoring program of PFC3D. The results show that the larger the effective joint area and larger the joint size inside the coal sample, the smaller the compressive strength of the coal sample. The increase of joint size and joint surface area increased the ductility and stress-strain curve multipeak phenomenon of the coal sample to some extent. During the rupture of the coal sample, the changes of each phase of the statistical curve of joint number and the phases of the stress-strain curve of the coal sample are compatible.